Induction of Flavonoid Synthesizing Enzymes by Light in Etiolated Pea (Pisum sativum cv. Midfreezer) Seedlings - Hrazdina, Geza (1982)
Etiolated pea (Pisum sativum cv. Midfreezer) seedlings respond to illumination with white light by changes in the activity of phenylpropanoid and flavonoid synthesizing enzymes. Unlike in cell cultures, changes in enzyme activity in pea seedlings are not concerted. Phenylalanine ammonia-lyase (EC 4.3.1.5) activity peaked approximately 18 hours after onset of illumination. The phenylacetate path did not interfere with the measurement of phenylalanine ammonia-lyase activity. Activity of cinnamic acid 4-hydroxylase (EC 1.14.13.11) showed an early peak after 8 hours illumination, declined thereafter sharply, then gradually increased during the remainder of the experiment. Activities of chalcone synthase and UDP glucose:flavonol 3-O-glucosyltransferase (EC 2.4.1.91) increased steadily and reached a plateau after approximately 70 hours illumination time. Activity of 4-hydroxycinnamate:coenzyme A ligase (EC 6.2.1.12) remained relatively unchanged, whereas that of chalcone isomerase (EC 5.5.1.6) declined steadily during the course of the experiment. The relative in vitro enzyme activities suggest that the rate-limiting step for the phenylpropanoid path is the cinnamic acid 4-hydroxylase, that of the flavonoid pathway is the chalcone synthase. Integration of enzyme activity curves, however, show that only the curve deriving from phenylanine ammonia-lyase activity matches closely the production of the flavonol glycosides.